Study on the spatial morphological evolution of traditional old urban centers based on space syntax and GIS spatial analysis: a case study of the Yiyang historical and cultural city protection zone - Wu, Yuxin; Yuan, Zhicheng; Ning, Qimeng; Deng, Geyang (Frontiers in Earth Science, 2025)
The historical and cultural city protection zone is the core carrying area of the old city center, which centrally preserves historical streets, traditional buildings and cultural relics in the process of urban development, and is a key space that reflects the continuity of the city’s historical context and carries the cultural memory of residents. This study employs GIS-based spatial analysis and space syntax theory, combined with relevant policy and planning documents, to process and interpret digitalized historical maps of five development stages (1948, 1967, 1990, 2015, and 2024) of the Yiyang Historic and Cultural City Protection Area. The results reveal that: 1) The spatial morphology of the protection area evolved from a single north-bank settlement along the Zi River into a complex cross-river network, with the road system transforming from disorderly patterns to a highly connected and organized structure. 2) The protection area has consistently remained at the urban core, witnessing the evolution of Yiyang’s old city center through five stages of development, and as a distinctive “local part,” it plays a vital role in promoting the sustainable development of the city’s overall structure. 3) The functional composition of the protection area has shifted from being predominantly residential to a diversified mix of residential, commercial, cultural, industrial, and administrative uses. The concentration of commercial and cultural activities has enhanced the vibrancy of streets and alleys, fostering high-quality development across multiple spatial scales. This study provides empirical evidence for understanding the spatial morphological evolution of old city centers with local historic districts in medium-sized cities like Yiyang and offers practical insights for future urban planning and renewal.